Prevalence of antibodies against HCV and risk behaviors in Basic Health Units users in a small town in the Brazilian semi-arid region - Vaz, Maria Tereza Estevam Vaz (2025)
Background and Objectives: Hepatitis C virus (HCV) infection is a relevant public health problem due to its prevalence and possible progression to cirrhosis and hepatocellular carcinoma. Although the use of direct-acting antivirals has decreased the incidence in recent years, identifying those infected remains a challenge for the elimination of HCV by 2030. The objective of this study was to estimate the prevalence of HCV antibody (anti-HCV), and describe the sociodemographic and behavioral risk factors associated with HCV infection in individuals in a small town in the Brazilian semi-arid region. Methods: Following a non-random sampling procedure, a cross-sectional study of 800 individuals in the waiting rooms of Basic Health Units (BHU) was conducted. After formal consent, a rapid screen test for anti-HCV (Immunochromatography)was carried out, and a questionnaire was applied to collect sociodemographic, clinical and risk behavior data. Results: Five tests were positive (0.62%; 95%CI 0.2 – 1.4%), four women and one man. All were over 60 years old (mean age of 69.4) and some risk behaviors in the past, use of glass syringes, surgery, or blood transfusion, were statistically associated with HCV exposure. Conclusion: In this study, a low prevalence of anti-HCV was observed, close to that estimated in recent studies. The antibody was more frequently positive in older individuals, aged over 60 years, who reported risky past behavior. Greater attention should be given to these individuals.